Competitive Recovery–Stress and Mood States in Mexican Youth Athletes - Reynoso-Sánchez, Luis Felipe; Pérez-Verduzco, Germán; Celestino-Sánchez, Miguel Ángel; López-Walle, Jeanette M.; Zamarripa, Jorge; Rangel-Colmenero, Blanca Rocío; Muñoz-Helú, Hussein; Hernández-Cruz, Germán (Frontiers in Psychology, 2021)
Background Monitoring recovery–stress balance in sport is becoming more relevant to prevent training maladaptation and reach the optimal performance for each athlete. The use of questionnaires that identify the athlete’s recovery–stress state have much acceptance in sports due to reliability and useful, furthermore for its low cost. Identifying possible differences between sport modalities and sex is important to determine specific needs and possible intervention ways to keep a recovery–stress balance. The aim was to analyze the differences in the recovery–stress state and mood states by sex and sport type during the competitive phase in young Mexican athletes. As a secondary objective, the psychometric properties of the Mexican version of the Recovery–Stress Questionnaire for Athletes (RESTQ-Sport) were analyzed. Methods A cross-sectional study was carried on with 461 athletes (61% women and 39% men), 17.95 (±1.2) years old, from six sports disciplines. The RESTQ-Sport and Profile of Mood States (POMS) were applied in a single moment. Differences by sex and sports modality were analyzed. RESTQ-Sport’s confirmatory factor analysis was performed after the stress and recovery theoretical structure of two stress (general and sport) and two recovery (general and sport) dimensions, and last, the concurrent validation with the POMS was carried on. Results Significant differences by sex were found in the General Recovery and Sport Stress dimensions of the RESTQ-Sport as well as Vigor factor of the POMS, being higher for men; furthermore, both the Sport Recovery dimension of RESTQ-Sport and Cholera and the Fatigue and Depression factors from POMS also had differences by sport type, showing a less recovery and high stress for individual sport athletes. Goodness-of-fit indexes of the model for the RESTQ-Sport were acceptable. Pearson’s correlation between questionnaires was moderate (p < 0.05). Conclusion The recovery–stress state shows differences in the function of sex and sport modality. More special attention is suggested for women and individual sport athletes. The higher punctuation for men compared with women in sport stress dimension did not negatively affect the recovery–stress balance for male athletes. Finally, the Mexican context adaptation of the RESTQ-Sport provides a psychometric instrument suitable to assess the recovery–stress balance in Mexican athletes.